The Effectiveness Of Picture and Picture in Teaching Writing of Descriptive Text at The Eightgrade Students of SMP PGRI 4 Malang in the Academic Year 2019/2020 - Hiasisntus Sustamin Jakung (ANFA MEDIATAMA, 2022)
The present study aims at exams the effectiveness of picture in teaching writing of descriptive text of the eighth -grade students of SMP PGRI IV Malang in the academic year 2019/2020. Teaching writing skill is recommended in Junior High School because writing is very important. In competence based on curriculum, students are to produce written texts based on certain genres. The research is carried out through quantitative research with an experimental method because the researcher gives treatment in teaching writing. In conducting the research, the researcher uses one group pre-test-post-test design. The researcher gave pre-test before treatment and post-test after treatment to get the data. In this research, the researcher took sixteen students as a sample. The result of the study shows that the score of pre-test was 71,25 while the mean score of post-test was 88,12 and the mean score of differentiate was 16,87. On the other side, it was found that the result of t-score is bigger than t-table (9,32 > 1,82) at the significant level of 0,05. Therefore, based on the hypothesis testing, we can conclude that the Alternative Hypothesis (Ha) is accepted while the Null Hypothesis (Ho) is rejected. Based on the result, it can be concluded that the using picture as a media is effective to increase students writing skill of the students’ of Junior High School, especially for the eighth grade of SMP PGRI 4 Malang. Based on this findings, it is suggested, that the teacher should try to apply an interesting media.